2022
DOI: 10.1002/1348-9585.12323
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of heat strain by wearing a long-sleeve fan-attached jacket in a hot or humid environment

Abstract: Objectives This study examined whether a fan‐attached jacket (FAJ) may mitigate the heat strain in hot or humid environment. Methods Nine healthy men engaged in 60‐min sessions on a bicycle ergometer (4 metabolic equivalents [METs] workload) in hot‐dry (40°C and 30% relative humidity) and warm‐humid (30°C and 85% relative humidity) environments. Both are equivalent to an approximately 29°C wet‐bulb globe temperature. The experiment was repeated—once wearing an ordinal j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Participants repeatedly performed the cycling exercise protocol, which consisted of one set of 5 min at a load of 1.5 watt/kgBM and 15 min at a load of 2.0 watt/kgBM at 60 rpm. This exercise was repeated until the Tre reached 38.50°C ( 16 ) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants repeatedly performed the cycling exercise protocol, which consisted of one set of 5 min at a load of 1.5 watt/kgBM and 15 min at a load of 2.0 watt/kgBM at 60 rpm. This exercise was repeated until the Tre reached 38.50°C ( 16 ) ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Post-exercise fanning in compensable heat stress has been proven to be an effective method to reduce the increased Tc and Tsk, accompanied by greater evaporative heat loss (15). Several previous studies have observed that fan-cooling jackets suppress the increased in both Tc and Tsk in hot indoor environments (16,17). However, its application has not been studied during recovery from hyperthermia in postexercise, and it is unclear whether it reduces Tc and Tsk more rapidly, which are elevated by exercise under high solar radiation.…”
Section: Introductionmentioning
confidence: 99%